Bionic PDMS film with hybrid superhydrophilic/superhydrophobic arrays for water harvest. Issue 3 (26th January 2018) - Wu, Yanchun; Li, Huilin; Wen, Lulu; Men, Dandan; Hang, Lifeng; Liu, Dilong; Liu, Guangqiang; Cai, Weiping; Lyu, Xianjun; Li, Yue
Abstract : This paper presents a cheap and facile strategy for fabricating hybrid superhydrophilic/superhydrophobic arrays on a flexible polydimethylsiloxane (PDMS) film to harvest water from fog efficiently. The hydrophobic PDMS film, which mimics the micro-/nanostructures on a beetle's back, was selected as the substrate, on which a hydrophilic silicon dioxide (SiO2 ) colloidal monolayer was fabricated through self-assembly. After reactive ion etching, the silicon dioxide microsphere arrangement changed from pristine hexagonal close packed into hexagonal non-close packed. The silicon dioxide microspheres demonstrated superhydrophilicity and functioned as masks. Patterned grooves were also formed on the PDMS film and displayed superhydrophobicity. The fabricated hybrid superhydrophilic/superhydrophobic array films exhibited extreme wettability contrast and excellent water-harvesting performance of 3660·5 mg/(cm 2 h), which is much better than that of bionic surfaces of the Namib Desert beetles' back reported by others. The bionic flexible films can be reproduced with low cost and can be applied in water-trapping tents, building coverings, water or organic vapor condensers and microfluidic channels.